Modern Outcomes Following Treatment of Hepatocellular Carcinoma in Hereditary Hemochromatosis: A Matched Cohort Study. (December 2019) - McPhail, Mark J.W.; Khorsandi, Shirin E.; Abbott, Laura; Al-Kadhimi, Gillian; Kane, Pauline; Karani, John; O'Grady, John; Heaton, Nigel; Bomford, Adrian; Suddle, Abid
Abstract : Objective: Hepatocellular carcinoma (HCC) is a complication of the common genetic condition hereditary hemochromatosis (HH). It is unknown whether HH as an etiology of liver disease impacts the outcome. We compared the results of liver transplantation (LT), surgical resection and locoregional therapies in a matched cohort study and investigated whether HH as an etiology has an impact on survival. Materials and Methods: Consecutive patients with HH and HCC (2000 to 2015) were compared with age, sex and Barcelona Clinic Liver Cancer (BCLC) stage-matched non-HH HCC cases. Patients were offered curative or noncurative treatment according to BCLC stage and Milan criteria. The primary endpoint was all-cause mortality. Results: A total of 102 patients (52 HH; total cohort median age: 67 [44 to 78] y, 97% male, Model for End-stage Liver Disease: 9 [5 to 31]) were studied with a median follow-up of 22 (3 to 126) months. Of the HH cases, the median serum ferritin at diagnosis of HCC was 326 (27 to 5718) μg/L and α-fetoprotein 33 (2 to 197, 926) kIU/L. Five-year survival for HH patients receiving curative therapy was 77% (80% for LT, 67% for resection/radiofrequency ablation), and 15% (23% for transarterial chemoembolization) for those undergoing noncurative therapy. Survival for HH patients compared with controls was similar (hazard ratio=0.949; P =0.839). On multivariate Cox regression survival analysis, BCLC stage, and diagnosis of ischemic heart disease (but not HH diagnosis) were independently associated with reduced survival. Conclusions: Patients with HCC and HH can achieve comparable survival rates following curative or LRT modalities to other liver diseases. The BCLC staging system accurately stratifies survival and excellent 5-year survival is possible following LT in selected patients.